컬링 호그 투 호그 각 구간 스위핑 시 근 동원 양상 및 스톤의 정지 위치 분석 - 권영일; Young-il Kwon; 김태완; Tae-whan Kim; 최상협; Sang-hyup Choi (Ch'eyuk kwahak yŏn'gu, 2021)
〔목적〕 컬링에서 구간별 스위핑 동작의 차이가 스톤의 이동 궤적과 근 활성에 어떤 차이를 보이는지 확인하여 컬링 스위핑 훈련에 기초적인 자료를 제공하는데 본 연구의 목적이 있다. 〔방법〕 각 구간별 스위핑을 시스톤의 멈춘 위치를 확인하여 스톤 간의 길이(진행거리)와 너비(진행방향)를 확인하고, 이를 기록하기 위해 기준표를 통해와 기록 작성표에 기록하였다. 또한, 총 12부위의 근육에 EMG를 부착하고 구간 시작과 끝나는 시점까지 각 구간 당 20번 씩 총 60번 스위핑을 하게 하였다. 스위핑을 하는 대상자가 세 구간 모두 같은 조건으로 최대한 스위핑을 할 수 있도록 요구하였다. 〔결과〕 연구결과, 스톤의 속도가 빠른 1, 2구간과 스톤의 속도가 느린 3구간의 근 동원양상이 다르게 나타났는데, 스톤이 느리게 움직일 때 힘을 많이 써 힘이 남은 다른 근육을 이용해 좀 더 스위핑에 집중하는 것을 확인할 수 있었으며, 컬링의 스위핑 동작은 대부분 상지의 여러 근육들이 골고루 사용되는 동작으로 상체근육의 발달에 적합한 종목이라는 것을 검증할 수 있었다. 또한 밀기시 우측 삼각근, 당기기 시 우측 상완삼두근의 근동원율이 높다는 것을 알 수 있었다. 〔결론〕 스톤의 구간별 스위핑 효과는 대기온습도의 변화, 아이스온도의 변화, 패블의 온도-크기-개수, 스톤의 엣지 상태-반발력 등에 따라 스톤이 움직이는 크기 각도 등이 변하는 변수가 많은 운동 종목으로 선수들의 많은 경험에 의하여 이러한 변수들에 대해 대처할 수가 있고 훈련이 필요할 것으로 판단된다. [Purpose] This is to provide essential data for training necessary for sweeping through the analysis of muscle activity generated at this time and how much sweeping and what trajectory moves the stone when the movement of the stone is controlled through sweeping. [Methods] To check and record the distance between the stones by checking the stop position of the stone made by sweeping each section, the length (progress distance) and width (progress direction) were recorded using a reference table and a record preparation table. With the EMG attached, a total of 60 sweeps were made 20 times each from the beginning of the section to the end of the section. Sweeping subjects were asked to sweep as much as possible under the same conditions in all three sections. [Results] As a result of the study, the muscle mobilization patterns of the 1st and 2nd sections of the stone with the faster speed and the 3rd section with the stone's slower speed appeared differently. It was confirmed that the sweeping motion of curling is a motion that is used evenly among the muscles of the upper extremity, and it can be verified that it is a suitable item for the development of upper body muscles. Also, the right deltoid's muscle activity rate during push and the right triceps brachii during pull was high. [Conclusions] Each section of the stone's sweeping effect is an exercise that has many variables, such as changes in atmospheric temperature and humidity, changes in ice temperature, temperature-size-number of pebbles, and the edge state-resilience of stones, etc. It is judged that experience can cope with these variables and requires training.